Vertical migration of nutrients and water-soluble organic matter in the soil profile under pre-sowing seed treatment with plant growth promoting rhizobacteria - Volkogon, Vitaliy V.; Potapenko, Lyudmyla V.; Volkogon, Mykola V. (Frontiers in Sustainable Food Systems, 2023)
Studies conducted in a stationary lysimeter experiment in the conditions of the washing water regime have shown that the use of PGPR for pre-sowing seed inoculation of agricultural crops reduces vertical migration of biogenic nutrients and water-soluble organic matter down the soil profile. The effect of seed inoculation with PGPR on the reduction of nutrient losses was not specific to the type of rhizobacteria and was similar for crops grown on different mineral fertilizers backgrounds (spring barley and winter rye seeds were inoculated with the nitrogen-fixing bacteria—Azospirillum brasilense 410 and A. brasilense 18-2, respectively, while maize seeds were inoculated with the phosphate-mobilizing Paenibacillus polymyxa KB). Seed inoculation has decreased nitrogen leaching down the soil profile by 4–9 kg/ha, phosphorus compounds—by 0.5–3.0 kg/ha, potassium—by 0.6–3.0 kg/ha, calcium—by 6–42 kg/ha, magnesium—by 3.0–6.0 kg/ha, water-soluble organic matter—by 0.8–8.0 kg/ha, subject to crop and norms of mineral fertilizers. Maize seeds inoculated with phosphorous-mobilizing P. polymyxa KB under crop cultivation on the cattle manure background did not affect the intensity of nutrient migration. On the other hand, the combination of green manure (narrow-leaved lupine as an intermediate crop) with pre-sowing seed inoculation had significantly reduced nutrient losses beyond the root zone soil layer. It is concluded that the use of PGPR in crop production on mineral and green manure backgrounds contributes to the preservation of soil fertility by limiting biogenic nutrients and water-soluble organic matter leaching with the water drainage down the soil profile. Pre-sowing seed inoculation had no significant effect on the vertical migration of nutrients in the soil on the background of cattle manure, due to the highly competitive environment created with the introduction of microorganisms from organic fertilizer, preventing the establishment of close interactions between PGPR and plants.